A Study of Chinese Traditional Opera and Its Decadency: A Comparative Analysis - Shen, Sitao (2013)
The cultural industry is becoming the pillar industry to support the further growth of developing country. With the expansion of economic crisis, people are more focus on the change of economic environment and ignore the decadency of some cultures. The Chinese traditional opera has experienced the continuously decline in the past few years. As the circumstance changed, traditional cultural art is gradually fading. The problem and difficulty that Chinese Opera has faced could be a typical example to illustrate the vital part of cultural industry is dying. Moreover, choosing Western Opera as the comparison object because it is close to Chinese Opera with regard to the formation. Therefore, the problems that Chinese Opera faced Western Opera also blighted. This paper through studying the history of these two art forms and interviewing related researcher, further analyse the current situation and raise corresponding solutions.